2016
DOI: 10.1177/0022034516667724
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Circuit Regulating Tooth Development in Crocodilians

Abstract: Alligators have robust regenerative potential for tooth renewal. In contrast, extant mammals can either renew their teeth once (diphyodont dentition, as found in humans) or not at all (monophyodont dentition, present in mice). Previously, the authors used multiple mitotic labeling to map putative stem cells in alligator dental laminae, which contain quiescent odontogenic progenitors. The authors demonstrated that alligator tooth cycle initiation is related to β-catenin/Wnt pathway activity in the dental lamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although scientific literature refers mostly to mammal species, recent publications confirm that these molecules play similar roles in reptile wound healing. Evidence derives from studies regarding growth factors under physiological conditions such as IGF-1 being widely expressed in reptile blood and tissues, [37][38][39][40] FGF playing a major role in crocodile teeth replacement, 41 crocodile oil containing TGF-b at concentrations proven to enhance wound healing and reduce scar formation. 42 Under pathological conditions, tissue IL-6 increases during inflammation in turtles, 43 PDGF is highly expressed in lizards spinal cord after tail amputation, 44 and VGEF contributes to gecko's wound healing and tail regrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Although scientific literature refers mostly to mammal species, recent publications confirm that these molecules play similar roles in reptile wound healing. Evidence derives from studies regarding growth factors under physiological conditions such as IGF-1 being widely expressed in reptile blood and tissues, [37][38][39][40] FGF playing a major role in crocodile teeth replacement, 41 crocodile oil containing TGF-b at concentrations proven to enhance wound healing and reduce scar formation. 42 Under pathological conditions, tissue IL-6 increases during inflammation in turtles, 43 PDGF is highly expressed in lizards spinal cord after tail amputation, 44 and VGEF contributes to gecko's wound healing and tail regrowth.…”
Section: Discussionmentioning
confidence: 99%
“…While teeth are replaced on a schedule that is independent of wear or damage 7 , the underlying regulatory mechanism of the replacement process has been difficult to understand. Within reptiles, modern studies of crocodilians—the only present-day toothed archosaurs—have demonstrated that the dental laminae within the alveoli (tooth sockets) form a niche of stem cells for the multiple generations of teeth, and that this mechanism is regulated by expression of a network of regulatory genes 8 , 9 . Even though our understanding of tooth development in extinct archosaurs, and its underlying regulatory mechanism, is still in its infancy, polyphyodonty has been documented for a range of extinct archosaurs 10 12 , including the toothed stem birds of the Mesozoic Era 13 15 .…”
Section: Introductionmentioning
confidence: 99%